The psychological and physiological impact of biophilic design elements on user satisfaction in interior spaces - حسين, هلا; هاني ودح; نسيبة سعيد (Latakia University Journal -Engineering Sciences Series, 2023)
The concept of biophilia (love of nature) appeared in the form of a new thought open to natural factors that have a high impact on the human psyche, to provide man with a method in which he feels comfortable and satisfied with natural life. This method works on the adoption of the biophilia factor, which can be considered as one of the factors with the highest impact, which is expected to be more effective in the internal architectural design and the psychological state of the users. The level of awareness of the importance of this relationship is the main preliminary factor for Identity, privacy, the advantage of open spaces and the aesthetic sense of the basic demographic needs and factors that improve mood and have a psychological impact on the user, and the element of nature, according to recent studies, plays a prominent role in promoting positive feelings within the space, and they are an important and reliable factor in improving satisfaction About the dwelling, the research aims at a thorough study of the concept of biophilic design and how to activate it within the void and to increase the interest in the importance of interaction between it and the psychological comfort of the user within the void.